Settlements of Trade Disputes between China and Latin American Countries
XIII, 215 p. 12 illus., 5 illus. in color.
Keywords: Presenting a wealth of highly original and innovative analyses and case studies, this book examines the strategic ties between various emerging economies, their different approaches to finding mutual trade solutions, and new trends in the use of contingent protection. The research methodology can also be applied to the study of specific Latin American countries or other developed or developing states in comparison to China. The book presents new theories and offers a valuable template for further studies in this area. Further, the application of the New Haven approach can further develop the studies' potential to offer guidance in a broader context.